Interpretacja humanistyczna dyskursów performatywnych - Tarnowski , Józef (Studia Europaea Gnesnensia, 2018)
Jerzy Kmita’s conception of humanistic interpretation is an appropriate reconstruction of communicative discourses, but it does not allow reconstruction of the non-communicative ones. In order to extend the range of application, I have employed John L. Austin’s performative-constative distinction, but have expanded its scope from speech acts to any discourses. As a result, the classification of discourse is as follows: explicit and implicit constatives, and explicit and implicit performatives. The efficacy of the new categorisation has been demonstrated with selected discourses sourced from the history of aesthetics.